Serotonin modulates excitatory synapse maturation in the developing prefrontal cortex - Roberto Ogelman; Luis E. Gomez Wulschner; Victoria M. Hoelscher; In-Wook Hwang; Victoria N. Chang; Won Chan Oh (Nature Communications, 2024)
Abstract Serotonin (5-HT) imbalances in the developing prefrontal cortex (PFC) are linked to long-term behavioral deficits. However, the synaptic mechanisms underlying 5-HT-mediated PFC development are unknown. We found that chemogenetic suppression and enhancement of 5-HT release in the PFC during the first two postnatal weeks decreased and increased the density and strength of excitatory spine synapses, respectively, on prefrontal layer 2/3 pyramidal neurons in mice. 5-HT release on single spines induced structural and functional long-term potentiation (LTP), requiring both 5-HT2A and 5-HT7 receptor signals, in a glutamatergic activity-independent manner. Notably, LTP-inducing 5-HT stimuli increased the long-term survival of newly formed spines ( ≥ 6 h) via 5-HT7 Gαs activation. Chronic treatment of mice with fluoxetine, a selective serotonin-reuptake inhibitor, during the first two weeks, but not the third week of postnatal development, increased the density and strength of excitatory synapses. The effect of fluoxetine on PFC synaptic alterations in vivo was abolished by 5-HT2A and 5-HT7 receptor antagonists. Our data describe a molecular basis of 5-HT-dependent excitatory synaptic plasticity at the level of single spines in the PFC during early postnatal development.